Creative Young Generation: Student Movement to Serve for More Advanced Village Innovation - Rendi Setiawan Purba; Sherly Kurniawati; Tarisa Nazlita Saragih; Syaddan Dintara Lubis (Jurma : Jurnal Program Mahasiswa Kreatif, 2023)
The evolving global context has brought profound changes in various aspects of life, including the dynamics of rural communities. Amid this transformation, the role of the younger generation is becoming increasingly vital in responding to the challenges and opportunities that arise. This research will use a qualitative approach to explore this. This approach will allow us to explore and deeply understand the experiences, views, and perspectives of students involved in the Gerakan Mahasiswa Mengabdi untuk Inovasi Desa Lebih Maju. This research reveals the vital role played by the younger generation, in this case students, in driving innovation and sustainable development in rural areas. By understanding the challenges, motivations, and impacts of their participation, we can design appropriate measures to advance a more advanced, inclusive, and sustainable village innovation movement.